(untitled) (Global Journal of Science Frontier Research, 2014)
Viruses are a major component of the biosphere, entering cells and genomes to insert their own genetic material. Herpesvirus lies hidden for years in the cells of the nervous system before emerging to cause herpes vesicles at the body surface. In the ’virosphere’ there are the retroviruses, whose RNA genome can be converted to DNA by the reverse transcriptase enzyme carried in their viral particles, integrating their genes into the host cell genome and becoming one with it. When, for any of a number of reasons, the host immune system undergoes degrees of immunosoppression, the virus can reactivate, replicate, and cause disease. Even when this does not occur, oncogenic virus latency can induce malignancy in host cells.